P3.378 STI Testing in Nulliparous Women During Intrauterine Device or System Initiation in CASH Clinics (Retrospective Audit). (13th July 2013) - Valarche, E; Browne, R
Abstract : Background: Nulliparous women are not always offered intrauterine (IU) method of contraception due to the traditional perception from health care providers that there will be an increased rate of complications (particularly, PID). We sought to evaluate the clinical practise and STI testing during the initiation of IU method in nulliparous women in Contraceptive and Sexual Health (CASH) clinics. Study Design: Electronic patient records were analysed for nulliparous women who had an IUD/IUS inserted between April 2011 and March 2012. The clinical practise was evaluated against local, FSRH and BASHH standards of care. Results: 423 women initiated intrauterine contraception 107 (25%) nulliparous. Majority (60%) were white UK ethnicity; Median aged 27 (range 15–49) years 32% aged < 25 years 24% had previous TOPs 21% done by clinical nurse specialist 73% Nova T380 inserted, 4%–Mirena IUS Only 7 patients had minimal side effects after procedure (abdominal discomfort) No uterine perforations occurred Follow up data available for 50% of patients Only 9 removals were recorded during study STI testing (Chlamydia and gonorrhoea, NAAT) done for 75 (70%) patients, and 2 Chlamydia positive patients were identified (treated within 2 weeks of diagnosis, both were asymptomatic). Conclusion: Our study demonstrated a successful practise of the use of the intrauterine contraception method in nulliparous women in an integrated CASH service. The prevalence of STI was 2.5% and screening prior or at the time of IU procedure should be one of many methods of prevention of STIs and health promotion in young population and also way of "pick up" of asymptomatic STIs. Our data did not show increased risk of pelvic infection in nulliparous women with initiation of IU contraception which prove to be safe and effective method of preventing of unplanned pregnancies.